Stylistics goes Historical. Current Trends and Practices in Historical Stylistics. Introduction - Montini, Donatella (Status Quaestionis, 2018)
Studies in Stylistics in the past few decades have branched out to include the most diverse contexts of language production and have drawn on a vast array of methodologies, leading to what has been acknowledged as its interdisciplinary turn. As occurred in other paradigms, the approach shifted from regarding language as a synchronic, static, and homogenous system to a diachronic, social, and dynamic entity. It is this interest in the diachronic dimension that eventually gave rise to studies into Historical Stylistics, or rather, a New Historical Stylistics, and, as a sister discipline, into Historical Pragmatics. Both fields of study have adapted methods and devices developed in Stylistics and Pragmatics to work on texts from the past (literary and otherwise) and on language use and variation in past contexts, in order to understand how meaning is made and supply new materials and evidence to linguists, historical linguists, and language historians. In the wake of such innovations in the approach to stylistic studies, the present issue of Status Quaestionis aims to take a closer and updated look to a select group of texts, literary and non-literary. The diversity of approaches that inform the essays is intended to reflect the varied critical scenario that marks contemporary stylistic studies and the different trends in the approach to reading texts here represented will also bring to light a number of key questions regarding the methods and outcomes of such readings or analysis.